2021
DOI: 10.3758/s13415-021-00896-8
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Task-Irrelevant Race Information is Associated with Diminished Cognitive Control in Black and White Individuals

Abstract: The race of an individual is a salient physical feature that is rapidly processed by the brain and can bias our perceptions of others. How the race of others explicitly impacts our actions toward them during intergroup contexts is not well understood. In the current study, we examined how task-irrelevant race information influences cognitive control in a go/no-go task in a community sample of Black (n = 54) and White (n = 51) participants. We examined the neural correlates of behavioral effects using functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 122 publications
(192 reference statements)
3
10
0
Order By: Relevance
“…Paralleling our behavioral findings, Black and White faces showed higher neural dissimilarity under uncertain threat, relative to uncertain reward or no uncertain event across all functionally defined brain networks (Yeo et al, 2011) in both Black and White participants. Greater neural dissimilarity in the threat state was The current behavioral findings add to a growing literature that suggests that exposure to Black faces can impair cognitive control processes and are consistent with findings of heightened behavioral reactivity to Black relative to White racial cues (Amodio et al, 2008;Correll et al, 2002;Payne, 2001;Rubien-Thomas et al, 2021). This study extends our knowledge of race-based reactivity to cues by experimentally manipulating uncertain threat and demonstrating that impulse control to Black faces is greatest under conditions of uncertain threat compared with conditions of no uncertainty or uncertain reward.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Paralleling our behavioral findings, Black and White faces showed higher neural dissimilarity under uncertain threat, relative to uncertain reward or no uncertain event across all functionally defined brain networks (Yeo et al, 2011) in both Black and White participants. Greater neural dissimilarity in the threat state was The current behavioral findings add to a growing literature that suggests that exposure to Black faces can impair cognitive control processes and are consistent with findings of heightened behavioral reactivity to Black relative to White racial cues (Amodio et al, 2008;Correll et al, 2002;Payne, 2001;Rubien-Thomas et al, 2021). This study extends our knowledge of race-based reactivity to cues by experimentally manipulating uncertain threat and demonstrating that impulse control to Black faces is greatest under conditions of uncertain threat compared with conditions of no uncertainty or uncertain reward.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings support the notion that race information interferes with goal-directed behavior when individuals anticipate uncertain threat. Previous work shows that negative implicit attitudes toward Black people are associated with altered frontoparietal activity (Brosch et al, 2013;Krill & Platek, 2009;Phelps et al, 2000;Rubien-Thomas et al, 2021) and diminished cognitive control Rubien-Thomas et al, 2021) upon exposure to Black faces. Accordingly, implicit bias may contribute to interference with goal-directed processing in the presence of race information related to stereotype-based threat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study by Fassett‐Carman et al (2022) revealed only a single association between independent SLEs and cortical thickness that survived correction, which was a cluster in lateral orbitofrontal cortex (though this was also detected for dependent SLEs). This region is involved in executing cognitive control within the context of emotion (Kuusinen et al, 2018; Rubien‐Thomas et al, 2021). We have argued that our behavioral measure (CANTAB) may be indexing dorsolateral aspects of EF, while our neural measure (MFTP) may be indexing dorsomedial functions.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, people face personal pressures—due to internal egalitarian values and external social pressures to comply with social norms—to self-monitor and regulate the expression of stereotypes and prejudice (Plant & Devine, 1998). This act of self-regulation to avoid appearing prejudiced has been shown to deplete subsequent cognitive functioning (Richeson et al, 2003; Richeson & Shelton, 2003; Richeson & Trawalter, 2005; Rubien-Thomas et al, 2021; Shelton & Richeson, 2005). For instance, one study found that after an interaction with a Black confederate, White participants performed worse on a subsequent decision-making task (i.e., Stroop task), presumably due to depleted cognitive resources from self-regulation during the preceding interracial interaction (Richeson & Shelton, 2003).…”
Section: The Current Studies: Experimental Paradigm and Predictionsmentioning
confidence: 99%